Australians' Experience of the COVID-19 Pandemic: Advantages and Challenges of Scaling Up Qualitative Research Using Large-Scale Rapid Analysis and Building Research Capacity Across Rural Australia. (11th February 2021) - Rolf, Floraidh; Campbell, Narelle; Thompson, Sandra; Argus, Geoff
Australia responded to the emergence of the COVID-19 global pandemic in 2020 by initiating a border and bio-security zone lockdown and policies emphasising social distancing and hand hygiene. To understand the public response to this, Southern Queensland Rural Health commenced a two-phase research project exploring attitudes and practices towards the COVID-19 pandemic in Australia. An initial online survey foreshadowed 90 qualitative interviews with respondents to explore what the pandemic meant for everyday life. This paper details use of a qualitative approach by a national collaborative of investigators from 9 rural university departments in Australia who came together to research the qualitative phase of the project. Our methodological approach aligned with extant literature describing the management of large-scale interviewing and coding in the context of unfolding and dynamic contexts. The 'RITA' model (Rapid Identification of Themes from Audio recordings) entails a five-step process designed to progress from identifying research foci, through deductive and iterative coding to identify key concepts. We used a combination of coding templates, organisation and tagging of field notes and real-time sharing through a secure cloud drive to create a data set for immersive analysis and generation of ideas. Use of this method has added to the collective knowledge about successful rapid research investigations, recognising the inherent tension between speed and rigour. This is not a binary but a dialectic; trustworthiness is integral to qualitative research. However, use of fresh approaches is accommodated by new technologies and can preserve adequate rigour while enabling collaboration, research capacity building and increasing the pace of data collection and analysis. This project has presented methodological challenges and highlights some strengths of such an approach. It is hoped that reporting our approach and experiences is useful for the broader health and research community considering large-scale qualitative research.